Glycosaminoglycans as polyelectrolytes: implications in bioactivity and assembly of biomedical devices. (3rd October 2022) - Costa, Rui R.; Reis, Rui L.; Pashkuleva, Iva
ABSTRACT : The innate negative charge of glycosaminoglycans (GAG) is in the origin of their bioactivity: it drives their spontaneous complexation with positively charged biomolecules and ions, regulating homeostatic functions by protein stabilization, protection and activation. Copycatting these interactions enables different supramolecular approaches towards the assembly of biofunctional devices. Such approaches allow processing under physiological conditions and thus, they are of unprecedented biocompliance for device build-up compared to conventional methods based on chemical cross-linkers, volatile and organic solvents, and high temperatures. We review different set-ups based on GAG electrostatic complexation and showcase their application towards the development of diverse therapeutic systems. We also discuss challenges associated with GAG complexation into intricate three-dimensional networks holding back the widespread use of these methods. Finally, we anticipate that conscious choice of GAG with distinct polyanionic strength and specific bioactivity will make possible the fabrication of constructs with personalized and customized properties in the nearest future.